Institutional Investment Horizons and the Cost of Equity Capital. Issue 2 (20th December 2012) - Attig, Najah; Cleary, Sean; El Ghoul, Sadok; Guedhami, Omrane
Abstract : We examine the influence of institutional investors' investment horizons on a firm's cost of equity. We argue that the cost of equity will decrease in the presence of institutional investors with longer‐term investment horizons due to improved monitoring and information quality. Our empirical results demonstrate that the cost of equity declines in the presence of institutional investors with long‐term investment horizons, all else remaining equal. Our results indicate also that the monitoring role of long‐term institutional investors is more pronounced for firms with higher agency problems (poorly governed firms). Overall, our evidence suggests that when considering the influence of institutional investors, it is critical to account for institutional heterogeneity, which leads to new directions for future research.